Pengaruh Efektifitas Sistem Pengendalian Intern Terhadap Kinerja Perkreditan Pada PT. Bank Bukopin Banda Aceh di Kota Banda Aceh (Studi pada PT. Bank Bukopin Banda Aceh di Kota Banda Aceh) - Eliana Eliana (Jurnal EMT KITA, 2017)
This research is an empirical study about the influence of effectiveness of internal finance to credit performance at PT. Bank Bukopin Banda Aceh. The purpose of this study is to determine the effect of internal finance effectiveness on credit performance at PT. Bank Bukopin Banda Aceh. Population in this research is all manager and employee of credit at PT. Bank Bukopin Banda Aceh, totaling 20 people. Data collection is done by distributing questionnaires that have been prepared to the respondent. Primary data were analyzed by using simple linear regression. The results explain the effectiveness of internal control significant effect on credit performance at PT. Bank Bukopin Banda Aceh. The role of variable effectiveness of internal control system on the performance of credit distribution at PT. Bank Bukopin Banda Aceh is more dominant than the role of other variables.